2023
DOI: 10.54055/ejtr.v34i.2992
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress in the Austrian tourism industry: hotels and restaurants analysis

Abstract: Considering the limited number of studies on the early detection of crises and insolvencies in the tourism industry, there are several research gaps. Therefore, this study analyzes which financial and non-financial variables significantly influence the financial distress of the tourism businesses (hotels and restaurants) in Austria. The resource-based and network-based views were used as theoretical foundations to determine which variables influence the probability of financial distress, with a total of 776 ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 156 publications
0
0
0
Order By: Relevance
“…In terms of failures, many studies have reported high percentages of firm failures in the hospitality industry in various countries (Abidin et al 2020;Boer 1992;Chathoth et al 2006;Pisula 2020;Situm 2023;Solnet et al 2010;Westgaard and van der Wijst 2001). An increased bankruptcy risk for the hotel sector may arise after the end of the COVID-19 period, as projected recently in a few studies (Crespí-Cladera et al 2021;Matejić et al 2022;Špiler et al 2022), as also due to the current energy and cost of living crises.…”
Section: Firm Failures In the Hotel Industry: Motivation For Sectoral...mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of failures, many studies have reported high percentages of firm failures in the hospitality industry in various countries (Abidin et al 2020;Boer 1992;Chathoth et al 2006;Pisula 2020;Situm 2023;Solnet et al 2010;Westgaard and van der Wijst 2001). An increased bankruptcy risk for the hotel sector may arise after the end of the COVID-19 period, as projected recently in a few studies (Crespí-Cladera et al 2021;Matejić et al 2022;Špiler et al 2022), as also due to the current energy and cost of living crises.…”
Section: Firm Failures In the Hotel Industry: Motivation For Sectoral...mentioning
confidence: 99%
“…Relatively recent reviews of hospitality financial management (Jang and Park 2011;Tsai et al 2011) have dedicated sections to firm bankruptcy, but at the time, the number of studies was more limited. More recently, Lado-Sestayo et al (2016, Falk and Hagsten (2018), Situm (2023) and Caires et al (2023) included literature review sections in their empirical work on hotel failure and presented cumulative tables of relevant studies, while Spyridou (2019) provided a conceptual approach regarding the same issue. The scope of discussing and presenting the literature in these six studies is not exhaustive on the nexus of financial factors and hotel default; rather, they included all the factors affecting tourism or hospitality firm defaults.…”
Section: Introductionmentioning
confidence: 99%